Analysis of Sharia Compliance on the Application of Reputational Risk in Service Marketing at Dompet Dhuafa - Retnowati, May Shinta; Silvi Kusumastuti, Annisa; Al-Huzwah, Fatya Zahwa (ASFA Foundation, 2025)
Risk management is a crucial aspect in maintaining the stability and reputation of non-bank Islamic financial institutions. This research focuses on the implementation of risk management, particularly related to reputation and donors, at Dompet Dhuafa East Java. This study employs a qualitative methodology using case study techniques to investigate how dompet dhuafa manages risk in order to minimize potential hazards that can harm the organization’s standing and donors’ confidence. The research results show that Dompet Dhuafa has undertaken several initiatives to identify, evaluate, and control risks, including the development of better monitoring procedures and reporting systems. However, challenges still arise in measuring the effectiveness of risk management, particularly in relation to reputation and donor satisfaction indicators. This research highlights the importance of enhancing leadership roles in building a strong risk awareness culture throughout the organization, as well as the need to refine the risk management framework to better align with the characteristics of Islamic financial institutions. This finding is expected to contribute to the development of more optimal risk management practices in non- bank Islamic financial institutions.